2020
DOI: 10.3819/ccbr.2020.150006
|View full text |Cite
|
Sign up to set email alerts
|

The importance of sensory perception in an elephant's cognitive world

Abstract: The three living species of elephants (Elephas maximus, Loxodonta africana, L. cyclotis) have evolved adaptive, sensory perceptual abilities to successfully navigate the physical and social environments in which they live. In this article, we review research evaluating the sensory perception of elephants across four sensory modalities-vision, audition, touch, and chemosensation. We also address how these sensory modalities have been incorporated into empirical investigations of elephant cognition. Last, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…This paper is not intended as a comprehensive review of what we know about elephant sensory perception (for that, see Ref. [14]). Instead, using general terminology intended for both a public and a scientific audience with open access to this paper, we present our perspective on encouraging active consideration of animal behavior and sensory perception in human-wildlife conflict mitigation and conservation efforts.…”
Section: This Paper's Purposementioning
confidence: 99%
See 3 more Smart Citations
“…This paper is not intended as a comprehensive review of what we know about elephant sensory perception (for that, see Ref. [14]). Instead, using general terminology intended for both a public and a scientific audience with open access to this paper, we present our perspective on encouraging active consideration of animal behavior and sensory perception in human-wildlife conflict mitigation and conservation efforts.…”
Section: This Paper's Purposementioning
confidence: 99%
“…Elephants rely on olfaction as one of their primary sensory modalities [12,14,[36][37][38]. They use olfactory information both to gather information about conspecifics [39] as well as to forage (e.g., [40]) with considerable research to date on the complexity of both functions.…”
Section: Sensory Systems and Communication: Some Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from both Asian and African elephant ethological research suggests that elephants likely have strong spatial and episodic memories. They appear to navigate complex physical and social environments over hundreds of miles using direct and indirect experience ( Jacobson and Plotnik, 2020 ). Other research has shown that elephants retain long-term memory of reward stimuli ( Markowitz et al, 1975 ), can identify and locate more than 100 out-of-view family members ( Bates et al, 2008 ), and can spatially locate waterholes over 100 km distances and extended periods of time (more than 3 years) ( Polansky et al, 2015 ).…”
Section: Complex Social Bonds Memory and Cognitive Abilitymentioning
confidence: 99%